Concomitant primary and secondary syphilis: A case series from std clinic, siriraj hospital - Sukhum Jiamton (2019)
© 2018, Faculty of Medicine Siriraj Hospital, Mahidol University. Objective: To emphasize the importance of dermatologists in identifying the presence of concomitant primary and secondary syphilis in the same patient in order to effectively diagnose the disease and provide adequate treatment. Case presentation: The diversity of the clinical manifestations of syphilis is very common; however, atypical presentations of syphilis have a chance to occur. Such concomitant primary and secondary syphilis, which develops chancre concomitant rash is an uncommon manifestation. Cases of atypical syphilis have been described most frequently in patients with concomitant human immunodeficiency virus (HIV) infection and men who have sex with men (MSM).This report presents the cases of 8 patients with primary and secondary syphilitic lesions. These cases are representative because of their clinical presentation, age range, gender distribution and diagnostic approach. Conclusion: The concomitant presence of primary and secondary syphilis in the same patient is unusual. The importance of our cases is to highlight some of the differences in clinical manifestations in HIV-infected men and HIV-uninfected men that might be important for early diagnosis for managing and curing such patients.